High-Salt Diet in the Pre- and Postweaning Periods Leads to Amygdala Oxidative Stress and Changes in Locomotion and Anxiety-Like Behaviors of Male Wistar Rats - Leal, Pedro Ernesto de Pinho Tavares; da Silva, Alexandre Alves; Rocha-Gomes, Arthur; Riul, Tania Regina; Cunha, Rennan Augusto; Reichetzeder, Christoph; Villela, Daniel Campos (Frontiers in Behavioral Neuroscience, 2022)
High-salt (HS) diets have recently been linked to oxidative stress in the brain, a fact that may be a precursor to behavioral changes, such as those involving anxiety-like behavior. However, to the best of our knowledge, no study has evaluated the amygdala redox status after consuming a HS diet in the pre- or postweaning periods. This study aimed to evaluate the amygdala redox status and anxiety-like behaviors in adulthood, after inclusion of HS diet in two periods: preconception, gestation, and lactation (preweaning); and only after weaning (postweaning). Initially, 18 females and 9 male Wistar rats received a standard (n = 9 females and 4 males) or a HS diet (n = 9 females and 5 males) for 120 days. After mating, females continued to receive the aforementioned diets during gestation and lactation. Weaning occurred at 21-day-old Wistar rats and the male offspring were subdivided: control-control (C-C)—offspring of standard diet fed dams who received a standard diet after weaning (n = 9–11), control-HS (C-HS)—offspring of standard diet fed dams who received a HS diet after weaning (n = 9–11), HS-C—offspring of HS diet fed dams who received a standard diet after weaning (n = 9–11), and HS-HS—offspring of HS diet fed dams who received a HS diet after weaning (n = 9–11). At adulthood, the male offspring performed the elevated plus maze and open field tests. At 152-day-old Wistar rats, the offspring were euthanized and the amygdala was removed for redox state analysis. The HS-HS group showed higher locomotion and rearing frequency in the open field test. These results indicate that this group developed hyperactivity. The C-HS group had a higher ratio of entries and time spent in the open arms of the elevated plus maze test in addition to a higher head-dipping frequency. These results suggest less anxiety-like behaviors. In the analysis of the redox state, less activity of antioxidant enzymes and higher levels of the thiobarbituric acid reactive substances (TBARS) in the amygdala were shown in the amygdala of animals that received a high-salt diet regardless of the period (pre- or postweaning). In conclusion, the high-salt diet promoted hyperactivity when administered in the pre- and postweaning periods. In animals that received only in the postweaning period, the addition of salt induced a reduction in anxiety-like behaviors. Also, regardless of the period, salt provided amygdala oxidative stress, which may be linked to the observed behaviors.